2019
DOI: 10.1111/jocs.14074
|View full text |Cite
|
Sign up to set email alerts
|

Permanent pacemaker insertion postmitral surgery: Do the atrial access and the origin of the sinoatrial node artery matter?

Abstract: Background and aim of the study To determine whether the type of atrial access to the mitral valve (left atriotomy, superior trans‐septal, or limited trans‐septal) influenced postoperative permanent pacemaker implantation and to investigate the effect of the sinoatrial (SA) node artery origin (right coronary or circumflex arteries) on the rate of pacemaker insertion. Methods We retrospectively reviewed consecutive cases of patients who had mitral valve surgery at the Trent Cardiac Centre (2008‐2016). The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In a retrospective study with 469 patients, Boulemden et al[ 3 ] reported that the surgical approaches to mitral valve surgery with the LA, TS, and STS approaches did not affect PPI. They also found that concomitant tricuspid valve surgery and advanced age (>70 years) were the main risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study with 469 patients, Boulemden et al[ 3 ] reported that the surgical approaches to mitral valve surgery with the LA, TS, and STS approaches did not affect PPI. They also found that concomitant tricuspid valve surgery and advanced age (>70 years) were the main risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the light of the current data, while the mitral valve is explored, SNA may be damaged due to its course, and rhythm disturbances may occur in the postoperative period. [ 3 , 4 ]…”
Section: Introductionmentioning
confidence: 99%